Pembuatan Website Konstruksi Osm (Operation System Monitoring ) Pt X (Modul L User Profile Dan Tomps N-Imon) - N, TIRTAZIA MEIGITA; DEWI, IRMA AMELIA (e-Proceeding FTI, 2024)
In recent years, advancements in web technology and user interface design have opened up new opportunities to create more intuitive and engaging user experiences on various types of websites. A website is a collection of interrelated web pages that are generally accessible via the internet. PT X is developing an Operational Support Management (OSM) application to facilitate easier access for its employees. This application is designed to streamline the management and monitoring of data, replacing the previous use of Google Docs and Google Sheets by PT X employees. Abstrak Dalam beberapa tahun terakhir, perkembangan teknologi web dan desain antarmuka pengguna telah membuka peluang baru dalam menciptakan pengalaman pengguna yang lebih intuitif dan menarik pada berbagai jenis website. Website adalah kumpulan halaman web yang saling terkait dan umumnya dapat diakses melalui internet.. PT X mengembangkan aplikasi OSM (Operational Support Management) guna memfasilitasi akses yang lebih mudah bagi para pegawainya. Aplikasi ini dirancang untuk memudahkan pengelolaan dan pemantauan data, menggantikan penggunaan google docs dan google sheets yang sebelumnya digunakan oleh pegawai PT X.